2003
DOI: 10.1080/110241598750004742
|View full text |Cite
|
Sign up to set email alerts
|

Complement activation and release of interleukin-6 and tumour necrosis factor-α in drained and systemic blood after major orthopaedic surgery

Abstract: Complement activation and IL-6 release after surgical trauma differ significantly in local and systemic blood samples. Conclusions based only on systemic findings may be limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…There was also no correlation with body mass index, comorbidity, surgical time, or complications of UTI, URTI, lower respiratory tract infection, or DVT. Autologous blood obtained from cell salvage systems also is associated with higher levels of IL-6 [1,20]. None of our patients had retransfusion of autologous blood.…”
Section: Discussionmentioning
confidence: 86%
“…There was also no correlation with body mass index, comorbidity, surgical time, or complications of UTI, URTI, lower respiratory tract infection, or DVT. Autologous blood obtained from cell salvage systems also is associated with higher levels of IL-6 [1,20]. None of our patients had retransfusion of autologous blood.…”
Section: Discussionmentioning
confidence: 86%
“…Recent studies have demonstrated that elective orthopedic surgery significantly elevates serum levels of interleukin-6 (IL-6) [1,5,7,10,11,13,16,[18][19]; in these circumstances, IL-6 rises rapidly in serum after the incision, peaking at 8-24 h. This increase has been attributed to the release of IL-6 from immunocompetent cells in the wound region [13,16], and it was found to significantly correlate with surgical trauma as defined by operation length and the volume of blood loss during surgery [13].…”
Section: Introductionmentioning
confidence: 99%
“…In another related study, no evidence was found for complement activation by classic or alternative pathway in hip replacement surgery [12].High levels of complement activation are recorded in blood samples taken from the drainage device immediately after operation for repair of thoracic scoliosis. Local activation of the complement was found to be 10 times greater than that in general systemic circulation [13].…”
Section: Resultsmentioning
confidence: 98%